Uporabnost koncepta ključnih besed kulture pri poučevanju kulturoloških vsebin in razvijanju medkulturne zmožnosti (na primeru vinske leksike) - Będkowska-Kopczyk, Agnieszka (Slavia Centralis, 2020)
THE CONCEPT OF CULTURAL KEY WORDS IN TEACHING CULTURAL CONTENT AND FOSTERING INTERCULTURAL COMPETENCE (EXEMPLIFIED BY WINE-RELATED VOCABULARY)In this article I present an approach to teaching Slovene culture and realities by means of words that are carriers of cultural meaning. Following Wierzbicka (1997), I define these words as cultural key words. The analysis focuses on the lexeme vino ‘wine’ and other linguistic units relevant to wine culture in Slovenia. The aim of the paper is twofold: 1) to prove the applicative value of research in the field of cultural linguistics in teaching cultural content, and 2) to illustrate how we can foster the intercultural competence of students by discussing with them the cultural background of wine-related vocabulary.
Keywords: cultural semantics; cultural key words; cultural meaning; Slovene culture; wine and wine culture; teaching cultural content